Context-dependent colonisation of Banksia species by arbuscular mycorrhizal fungi across contrasting rainfall regions - Zhao Zhang; Ling-Ling Chen; Duccio Migliorini; Felipe E. Albornoz; Patrick M. Finnegan; Kosala Ranathunge; Hans Lambers (Plant and Soil, 2026)
Background and aims The absence of a suberised exodermis in Banksia (Proteaceae) roots enables rapid carboxylate release for phosphorus mobilisation but also increases their susceptibility to soil pathogens. Recently, evidence of arbuscular mycorrhizal (AM) colonisation in Banksia species from high-rainfall regions prompted a reassessment of the association between Banksia species and AM fungi. Methods We collected root and soil samples from Banksia attenuata and B. sessilis at two contrasting rainfall sites to characterise the AM fungal communities. We also isolated oomycetes from the soil samples and conducted a glasshouse experiment using the native soils to verify the presence of viable AM fungi. Results At the high-rainfall Warren site, both Banksia species showed AM colonisation and five oomycetes were isolated, whereas no colonisation and only one oomycete occurred at the drier Jurien Bay site. In both species, AM fungal alpha diversity was lower in root samples than in soil samples, with roots dominated by Glomeraceae and soils enriched in Gigasporaceae and Acaulosporaceae. Additionally, Endogonaceae occurred in B. attenuata roots but were largely absent from B. sessilis . Conclusion These results demonstrate that the two Banksia species maintain context-dependent mycorrhizal associations under moist conditions, challenging their conventional classification as non-mycorrhizal.